Effect of Recombinant Gonadotropin on Testicular Function and Testicular Sperm Extraction in Five Cases of NR0B1 (DAX1) Pathogenic Variants - Teoli, Jordan; Mezzarobba, Vincent; Renault, Lucie; Mallet, Delphine; Lejeune, Hervé; Chatelain, Pierre; Tixier, Frédérique; Nicolino, Marc; Peretti, Noël; Giscard D’estaing, Sandrine; Cuzin, Béatrice; Dijoud, Frédérique; et al. (Frontiers in Endocrinology, 2022)
Background NR0B1 pathogenic variants can cause congenital adrenal hypoplasia or primary adrenal insufficiency in early childhood usually associated with hypogonadotropic hypogonadism. NR0B1 is necessary for organogenesis of the adrenal cortex and to maintain normal spermatogenesis. In humans, restoration of fertility in patients carrying NR0B1 pathogenic variants is challenging. Objective The aim of the study was to investigate the clinical, hormonal, histological, spermiological, and molecular genetic characteristics of a cohort of patients with NR0B1 pathogenic variants, monitored for fertility preservation. Patients We included five patients, including four teenagers, with NR0B1 pathogenic or likely pathogenic variants. They all had primary adrenal insufficiency and were receiving replacement therapy with glucocorticoids and mineralocorticoids. Patients received recombinant follicle-stimulating hormone and recombinant human chorionic gonadotropin in order to induce spermatogenesis. Combined gonadotropin treatment was initiated between 13 years and 15 years and 6 months for the four teenagers and at 31 years and 2 months for the only adult. Physical and hormonal assessments were performed just before starting gonadotropin treatment. After 12 months of gonadotropin treatment, physical examination and hormonal assessments were repeated, and semen analyses were performed. If no sperm cells were observed in at least 2 semen collections at 3-month interval, testicular biopsy for testicular sperm extraction was proposed. Results Bilateral testicular volume increased from 8 ml (interquartile range, 6–9) to 12 ml (10–16) after gonadotropin treatment. Inhibin B levels were relatively stable: 110 ng/L (46–139) before and 91 ng/L (20–120) at the end of gonadotropin treatment. Azoospermia was observed in all semen analyses for all cases during gonadotropin treatment. Three patients agreed to testicular biopsy; no mature sperm cells could be retrieved in any. Conclusion We characterized a cohort of patients with NR0B1 pathogenic or likely pathogenic variants for fertility preservation by recombinant gonadotropin treatment, which began either at puberty or in adulthood. No sperm cells could be retrieved in semen samples or testicular biopsy even after gonadotropin treatment, indicating that gonadotropin treatment, even when started at puberty, is ineffective for restoring fertility.